Imentation of Article 70 of Law on Sexual Violence Criminal Acts Number 12 Of 2022 on The Protection of The Rights of Child Victims of Sexual Violence In DP2KBP3A - Ramaida, Rizka Amalia; Handayani, Emi Puasa; Chasanah, Nur (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2024)
Sexual violence according to End Child Prostitution in Asia Tourism International is an interaction between a child and adults such as strangers, grandparents, parents, and siblings. Where the condition of the child is used as an object of lust for the perpetrator. The rise of sexual violence cases in Indonesia has concerned the community and the local government. Seeing the high rate of sexual violence is a slap in the face for the government, which should think of the best solution to protect children as the nation's next generation. Therefore, the ratification of the Sexual Violence Law Number 12 of 2022 is used as a preventive solution from the government to protect the rights of victims of sexual violence. The research method used by the current author is empirical and also a qualitative approach. And also the data collection technique is carried out by interview techniques and also a form of questionnaire. In implementing the protection of children's rights, the Women and Children Protection Team provides mental rehabilitation services, social rehabilitation for victims. In the last three years, sexual violence in kediri has decreased in 2023 to 13%. In addition, they also seek protection preventively or repressively. The research was conducted at (Office of Population Control Family Planning Women's Empowerment and Child Protection). Located at Jalan Panglima Sudirman 141 Kampung Dalem Village no 45 Kota.